Efficacy of Terbinafine Versus Itraconazole in the Treatment of Tinea Corporis - Hafeez, Sumreen (Journal of Pakistan Association of Dermatologists, 2025)
Background: Tinea corporis, sometimes referred to as ’ringworm,’ is a superficial illness caused by dermatophytes that affects the skin. Objective: To compare the efficacy of terbinafine versus Itraconazole in the treatment of tinea corporis. Methods: This Randomized Control Trail was conducted at Department of Dermatology, DHQ Hospital ,Sheikhupura, during the duration of July 2023 till December 2023. Total 50 cases (25 in both groups) with Tinea corporis were included. Then patients were randomly divided into two groups. In group A, patients were given terbinafine. In group B, patients were given itraconazole. Then, the patients were followed-up for 2, 4, 6 and 8 weeks. On each visit, patients were examined for complete resolution of tinea, by using total body surface area index and they were assessed for resolution of leions. All the data was recorded in proforma and then entered & analyzed through SPSS version 26. Results: In the terbinafine group, the mean age of the patients was 35.16 ± 8.76 years. In the itraconazole group, the mean age of the patients was 28.36 ± 10.65 years. In the terbinafine group, there were 15 (60%) males and 10 (40%) females. Whereas, in the itraconazole group, there were 8 (32%) males and 17 (68%) females. Moreover, in the terbinafine group, the baseline BSI score was 6.44 ± 3.19 and this score was reduced to 3.64 + 2.11 after 4 weeks of treatment. In this group the efficacy (complete cure within 4 weeks) was achieved in 6 (24%) cases. On the other hand, in the itraconazole group, the baseline BSI score was 7.20 ± 2.99, which was reduced to 1.75 + 0.50 after 4 weeks of treatment and the efficacy (complete cure within 4 weeks) was achieved in 13(52%) cases in this group. Conclusion: We found that itraconazole has better efficacy than terbinafine for tinea corporis. Thus in future, itraconazole can be a drug of choice for such cases.